2016
DOI: 10.1103/physreva.93.022501
|View full text |Cite
|
Sign up to set email alerts
|

Collision-induced line-shape effects limiting the accuracy in Doppler-limited spectroscopy ofH2

Abstract: Recent advances in theoretical calculations of H2 dissociation energies and ultra-accurate measurements of H2 transition frequencies give unprecedented possibilities not only for testing quantum electrodynamics (QED) and relativistic effects, but also for searching new physics beyond the standard model. In this paper we show that at the level of 10 −4 cm −1 the uncertainty of the Dopplerlimited H2 line position determination is dominated by collisional line-shape effects, which has not been taken into account … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 63 publications
(103 reference statements)
0
16
0
Order By: Relevance
“…It is clearly observed that the simple phenomenological HC kernel does not account for the angle and initial velocity dependencies and can differ from the real kernel by more than one order of magnitude. These unphysical properties of the HC kernel are clearly observed in experimental spectra analysis as an inability to properly reproduce the shapes of molecular hydrogen rovibrational lines in a wide range of pressures [15,16,[42][43][44]. It should be emphasized that the BB kernel also correctly handles the strong mass dependence of the kernel, whereas the HC kernel does not even depend on α.…”
Section: The Collisional Operatorŝ Fmentioning
confidence: 99%
See 2 more Smart Citations
“…It is clearly observed that the simple phenomenological HC kernel does not account for the angle and initial velocity dependencies and can differ from the real kernel by more than one order of magnitude. These unphysical properties of the HC kernel are clearly observed in experimental spectra analysis as an inability to properly reproduce the shapes of molecular hydrogen rovibrational lines in a wide range of pressures [15,16,[42][43][44]. It should be emphasized that the BB kernel also correctly handles the strong mass dependence of the kernel, whereas the HC kernel does not even depend on α.…”
Section: The Collisional Operatorŝ Fmentioning
confidence: 99%
“…The hard-collision model is insufficient for a proper description of the velocity-changing collisions in the modeling of the shapes of molecular resonances, in particular, the shapes of molecular hydrogen lines [15,16,[42][43][44]. The phenomenological hard-collision kernel, Eq.…”
Section: The Collisional Operatorŝ Fmentioning
confidence: 99%
See 1 more Smart Citation
“…[11] based on the analysis that merged both ab initio calculations and high-pressure measurement. This allowed us to reduce the systematic effects related to collisional perturbation to the shapes of molecular lines [15]. Despite operating in the Doppler-limited regime we reached 40 kHz of statistical uncertainty and 161 kHz of absolute accuracy of the S(2) 2-0 transition energy determination achieving the highest accuracy for homonuclear isotopologues of molecular hydrogen and only 3.2 times lower accuracy compared to the most accurate sub-Doppler measurements in HD [7] whose line intensities are almost 3 orders of magnitude stronger [7,22].…”
Section: Introductionmentioning
confidence: 99%
“…It also enabled to estimate possible systematic errors on Doppler width measurements [149] for the spectroscopic determination of the Boltzmann constant (cf also Sec. 5.2.1) and to determine the frequencies of unperturbed rovibrational transitions [152]. This profile was also used [153] to rescale the narrowing parameter of the HC model and improve the treatment of velocity-changing collisions in the Hartmann-Tran profile (Sec.…”
Section: 22b the Billiard-ball (Bb) Approximation For The Velocitymentioning
confidence: 99%